2001
DOI: 10.2527/2001.7971650x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inorganic and organic copper supplemented to first-calf cows on cow reproduction and calf health and performance.

Abstract: Two experiments were conducted to determine whether the supplementation of Cu in the organic or inorganic form to 2-yr-old cows, before and after calving, affects reproduction rate, calf health and performance, passive transfer of immunoglobulin, or liver and serum Cu concentrations compared with unsupplemented controls. Cows (n = 75 in 1997; n = 120 in 1998) were randomly assigned by estimated calving date and body condition score to one of three treatments: 1) Control, control; 2) Inorganic, inorganic Cu sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 0 publications
5
58
0
3
Order By: Relevance
“…Based on these results, one could hypothesize that transplacental transfer of Cu, or the ability of the developing foetus to exploit Cu from the mother organism, is partly limited. This is however in contrast with results suggesting that organ Cu concentrations of calves during gestation and early after calving are higher than those of their mothers (Gooneratne and Christensen 1989;Illek and Such˘1993;Muehlenbein et al 2001). The lower blood Cu concentrations of calves compared with their mothers may be due to the fact that in newborn calves ceruroplasmin, the main form of Cu transport in blood, is not produced to a sufficient extent (Roy 1980;Underwood and Suttle 1999).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Based on these results, one could hypothesize that transplacental transfer of Cu, or the ability of the developing foetus to exploit Cu from the mother organism, is partly limited. This is however in contrast with results suggesting that organ Cu concentrations of calves during gestation and early after calving are higher than those of their mothers (Gooneratne and Christensen 1989;Illek and Such˘1993;Muehlenbein et al 2001). The lower blood Cu concentrations of calves compared with their mothers may be due to the fact that in newborn calves ceruroplasmin, the main form of Cu transport in blood, is not produced to a sufficient extent (Roy 1980;Underwood and Suttle 1999).…”
Section: Discussionmentioning
confidence: 73%
“…Despite the fact that according to our results, Cu, compared with Zn, is not cumulated in colostrum to any significant extent, the results pointing to a trend towards correlation between colostral and blood Cu concentration of calves at the end of the period of colostral nutrition suggest that colostrum is an important source of Cu for calves. A prominent upward trend in Cu concentration of calves in the first month after calving has been described by Muehlenbein et al (2001), too.…”
Section: Discussionmentioning
confidence: 88%
“…reported that control calves had higher secondary antibody response to pig erythrocytes than copper, molybdenum and iron supplemented calves. Muehlenbein et al (2001) reported that administration of copper had no effect on incidence of neonatal diseases. In the present study, no significant differences were detected in incidence of neonatal diseases and days of treatment due to administration of iron and copper.…”
Section: Discussionmentioning
confidence: 99%
“…But Zn levels were insufficient for the late pregnancy and early lactation periods. This is probably so because large quantities of Zn are used up by the developing foetus and because high concentrations of Zn are present also in colostrum and milk (Muehlenbein et al, 2001;Kracmar et al, 2003;Pavlata et al, 2004b). It seems that in the last stage of pregnancy and around calving, dams lose more Zn than they ingest, their Zn reserves are depleted and Zn plasma concentrations decrease.…”
Section: Discussionmentioning
confidence: 99%